Kebijakan Publik Dalam Meningkatkan Pelayanan Sebagai Implementasi Otonomi Daerah Di Kota Denpasar - I Nyoman Artayasa (Universitas Mahendradatta Denpasar, 2020)
Policy of regional autonomy was born with the aim to keep the government and theintegrity of the Unitary Republic of Indonesia (NKRI), by encouraging the ability of initiativeand creativity of local government and local communities in the pursuit of prosperity.PublicPolicy is whatever governments choose to do or not todo. The principle of public service is toprovide a service with a good quality to the community which embodies the obligation of thegovernment apparatus as a public servant. Regional autonomy gives authority to localgovernment in this case the city government to explore potential areas to improve the quality ofservice to the community. In providing good service to the community, Denpasar governmentadopt local wisdom that philosophy Sewaka Dharma. Sewaka Dharma can be defined as